Effect of impeller speed and viscosity on whey lactose hydrolysis and β-galactosidase stability - Demirhan, Elcin; Apar, Dilek Kilic; Ozbek, Belma (TAYLOR & FRANCIS INC, 2007)
In the present work, the effects of impeller speed and viscosity on the enzymatic hydrolysis of whey lactose and enzyme inactivation were studied. The experiments were carried out in 250 mL of 25 mM phosphate buffer solution containing 50 g/L whey lactose by using a commercial beta-galactosidase produced from Kluyveromyces marxianus in a batch reactor system. The degree of lactose hydrolysis (%) and residual enzyme activity (%) was investigated versus impeller speeds from 100 to 600 rpm and viscosities from 1.005 to 13.43 cp for 30 minutes of processing time. The mathematical models depending on these process parameters were derived using the experimental data of residual lactose concentration and residual b-galactosidase activity. The predicted models have been confirmed with the experimental results.
Keywords: hydrolysis; impeller speed; beta-galactosidase; modeling; viscosity; whey lactose; ALPHA-AMYLASE; KLUYVEROMYCES-FRAGILIS; STARCH HYDROLYSIS; ESCHERICHIA-COLI; PERMEATE; KINETICS; Engineering